Perspective: Microbial hydrogen metabolism in rock-hosted ecosystems - Boyd, Eric S.; Colman, Daniel R.; Templeton, Alexis S. (Frontiers in Energy Research, 2024)
Hydrogen (H2) is among the most common and widely utilized electron donors in microbial metabolism. This is particularly true for microorganisms that inhabit subsurface environments where H2 concentrations can be high due to H2 generation via one or more abiotic and biotic processes, such as serpentinization, radiolysis, cataclasis, and microbial fermentation. A surge in interest in the exploration for and exploitation of geologic (i.e., white and orange) H2 as a clean low carbon fuel therefore necessitates an evaluation of the influence of microorganisms on its flux and potential recovery from subsurface systems. The widespread application of high throughput metagenomic sequencing approaches to rock-hosted ecosystems now makes it possible to readily identify microorganisms that harbor the potential to metabolize H2 and to predict their mode of coupling H2 oxidation with available oxidants using comparative genomic data from natural samples alone. When combined with several recent reports of measured rates of net microbial H2 consumption in rock-hosted ecosystems, such information provides new perspective on the potential for microorganisms to impact the economics of H2 recovery from geologic systems. In this perspective, the different classes of enzymes that microorganisms use to reversibly oxidize H2 to fuel their energy metabolism are introduced and their distribution in several rock-hosted ecosystems is discussed. A compilation of net microbial H2 oxidation activities in rock-hosted ecosystems is also presented to enable estimates of potential H2 loss from natural or stimulated geologic reservoirs during mining activities, with an example provided from the Samail Ophiolite that indicates >90% of geologic H2 produced could be lost to microbial consumption. Finally, avenues to guide future microbial research in environments where geologic H2 mining is planned are discussed.